Penerapan Logika Fuzzy Sugeno Dalam Memprediksi Besar Komisi Penghasilan Pada Toko Karunia Ijo Di Malang - Dimas Maulana Hakim; Tri Hastono; Yanuar Arifia Ranggana (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2024)
Abstract. Karunia Ijo sewing equipment shop in Malang is a place that has an important role in supporting the creative industry, especially in the fields of fashion and handicrafts. In this shop, we find various kinds of sewing equipment that are really needed by professional tailors, hobbyists and convection business people. This research aims to determine the amount of commission at the Karunia Ijo sewing equipment shop in Malang by considering the factors that influence the amount of commission on purchases. This research was conducted using the Sugeno method of fuzzy logic by determining the price of goods, purchase time, and volume of goods as the input, and the amount of commission as the output. The steps taken in this research are determining the degree of membership of each set of input variables which is referred to as fuzzyfication, then determining fuzzy rules, and carrying out fuzzification to get the final value in the form of the output of the purchase commission amount. The test result using Matlab was 5 while the result from manual calculations was 4.81. There is a slight difference, namely a difference of 0.19 but it is still in the large output category.